Levantamento e caracterização da entomofauna associada ao cultivo de eucalipto no estado de Alagoas - Gonzaga, Elmadã Pereira (2019)
The eucalyptus crop has been a great contribution to the economic activity in Brazil, due to its adaptability to the most varied soils and climates, in addition to its fast growth. The implantation of forest stands of Eucalyptus spp. in the state of Alagoas, is still recent but promising for the diversification of crops and biomass production in the region. However, due to host abundance and the use of clonal forest stands, which contribute to low genetic diversity, the occurrence of native and exotic pest insects becomes frequent. Thus, the present work had the objective to perform the survey and characterization of the entomofauna associated with the hybrid E. urograndis in the state of Alagoas. For the survey, manual collection and pitfall traps were used in an experimental clonal forest stand of E. urograndis (TP361, VCC865, I144 and VE41 clone). Through manual collection, 619 individuals were collected, distributed in 10 orders and 46 taxa. The order Coleoptera presented the highest number of insects collected 30.04%, followed by Hemiptera 23.58%, Araneae 14.53%, Hymenoptera 13.73% and Diptera 12.27%. During the evaluation period, a population outbreak of Costalimaita ferruginea (Coleoptera: Chrysomelidae) was identified in all clones evaluated. The taxa with the highest indexes of dominance, abundance, frequency and constancy, for all clones, were Aranaeae, Formicidae and Cicadellidae. The I144 clone showed the highest diversity index of Shannon-Weaner. In the pitfall survey, 5,960 individuals were collected in 15 taxonomic groups, where Formicidae, Araneae and Cicadellidae showed higher rates of dominance, abundance, frequency and constancy in all the clones evaluated. The VE41 clone had the highest diversity index of Shannon-Weaner. During the evaluation period, it was possible to report the constant occurrence of ants of the genus Atta, considered to be major pest insects in the Eucalyptus spp. crops.